2002
DOI: 10.1002/hipo.10007.abs
|View full text |Cite
|
Sign up to set email alerts
|

Genetic approach to variability of memory systems: Analysis of place vs. response learning and Fos-related expression in hippocampal and striatal areas of C57BL/6 and DBA/2 mice

Abstract: C57 and DBA mice were trained in a crossed maze to assess possible strain differences in place or response learning as a function of training duration (8 or 17 days) and extramaze cueing conditions. The first condition consisted of a diffuse visually cued environment (rich cueing). The second was the same plus an explicit visual cue marking the direction of the baited arm (rich cueing plus cue). The third was a featureless environment (poor cueing). During training, mice were released from the south arm and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
3
17
0
Order By: Relevance
“…1). This possibility is in accord with reports of less efficient learning in an environment in which the two learning strategies of declarative/place-based and procedural/response-based learning can interact competitively (25) and that WT C57BL/6 mice are "essentially place learners" (33)(34)(35). By this view, the abundance of spatial cues in the original maze task did not impair the performance of the Foxp2 hum/hum mice, which might have dealt more effectively with competition between the two available learning strategies.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1). This possibility is in accord with reports of less efficient learning in an environment in which the two learning strategies of declarative/place-based and procedural/response-based learning can interact competitively (25) and that WT C57BL/6 mice are "essentially place learners" (33)(34)(35). By this view, the abundance of spatial cues in the original maze task did not impair the performance of the Foxp2 hum/hum mice, which might have dealt more effectively with competition between the two available learning strategies.…”
Section: Resultssupporting
confidence: 88%
“…Given this result, we turned to a cross-maze task often used to discriminate place-based from response-based learning (15,17,25). We chose a Tolman variation of the task (16,36), tailored for our purposes, because the cross-maze variation by Packard and McGaugh (15) has been reported to be difficult for mice (33)(34)(35). In this cross-maze paradigm, we were able to test declarative/place-based learning and procedural/response-based learning separately as well as to challenge the interaction between them by testing the ability to change between place-based and response-based learning.…”
Section: Resultsmentioning
confidence: 99%
“…It seems now rather well established that rats strongly favour response strategy after extended training in a dual-solution task tested on in a cross-maze (Ritchie et al, 1950;Restle, 1957;Hicks, 1964;Mitchell and Hall, 1988;Packard and McGaugh, 1996;Oliveira et al, 1997;Passino et al, 2002;Yin and Knowlton, 2004). The present results showing that 74% of the control rats exhibited a response strategy during the second probe trial, confi rmed these previous fi ndings.…”
Section: Response Strategies and Extended Trainingsupporting
confidence: 89%
“…A large number of studies have shown that the use of place and response strategies early in training depends largely on intra-and extra-maze cue arrangements and densities (Tolman et al, 1946(Tolman et al, , 1947Restle, 1957;Oliveira et al, 1997;Passino et al, 2002;Canal et al, 2005). The capacity to use environmental cues to drive the behaviour (i.e.…”
Section: The Use Of Place Versus Response Strategies Early In Trainingmentioning
confidence: 99%
“…C57BL/6 and DBA/2 inbred mice have previously been used as a genetic animal model for anxiety-related and depression-like behavior (Crawley et al, 1997;Griebel et al, 1997;Ohl et al, 2003;Jacobson and Cryan, 2007) as well as a model of distinct hippocampal functioning regarding learning and memory (Ammassari-Teule et al, 2000;Passino et al, 2002). Moreover, it has been reported that mice of both strains show differences in glucocorticoid hormone responses towards stress but not under basal conditions (Cabib et al, 1990;Jones et al, 1998;McNamara et al, 2003;Shanks et al, 1990).…”
Section: Introductionmentioning
confidence: 99%